Natural born angel : an Immortal city novel - Speer, Scott, 1982- (Speer, Scott, 1982- Immortal city novel, 2013)
Maddy has been juggling her life of high school, family, and friends with the demands of being Angel Jacks Godspeed's girlfriend, but as war threatens, she must choose her Angel side or her human one, once and for all.